Archiwum literackie Wincentego Różańskiego w świetle założeń krytyki genetycznej - Przybyszewska, Alicja (Biblioteka Uniwersytecka w Poznaniu, 2017)
Tekst prezentuje spuściznę literacką Wincentego Różańskiego jako materiał badawczy dla krytyki genetycznej. Jest to metodologia pracy dokumentacyjnej, interpretacji i edycji, stawiająca w polu zainteresowania analizę genetyczną tekstu, przygotowanie genetycznego dossier oraz edycję, której celem jest rekonstrukcja etapów powstawania tekstu w formie cyfrowego wydania naukowego. Krytycy genetyczni poddają zatem wnikliwemu oglądowi bruliony i autografy, wprowadzają do badawczego instrumentarium pojęcie przed-tekstu, na który składają się różne wersje tekstu oraz wszelkie notatki i uzupełnienia autora, znajdujące się w obrębie rękopisu. Owe warianty, nie tekst zwany ostatecznym, stanowią w tej koncepcji klucz do zrozumienia procesu twórczego i odkrycia innej historii literatury niż ta, którą ustanawia się na podstawie drukowanego dorobku twórców. Archiwum twórcze Różańskiego, znajdujące się w zbiorach Ośrodka Dokumentacji Wielkopolskiego Środowiska Literackiego (Domu Literatury Biblioteki Raczyńskich), tworzą setki nieopublikowanych, pozostawionych w rękopisach wierszy poety. Stanowią one znakomity materiał do analizy i – być może – wydania genetycznego, którego koncepcję dotyczącą ineditów zaproponował francuski teoretyk badania genezy Pierre-Marc de Biasi.

The author discusses the literary output of Wincenty Różański presenting it as appropriate study material for genetic criticism. Genetic criticism is one of the most interesting approaches to the interpretation of texts and to the reconstruction of creative process. It is a kind of a methodology of examining tangible documents such as writer’s notes, drafts and corrections to help interpret the movement of writing that must be inferred from them and is primarily focused on the genetic analysis of the text, preparation of a genetic dossier and an investigation that is aimed at a reconstruction the stages in the origination of a text in the form of a digital research edition. Genetic critics are then primarily interested in notes and autographs in their penetrative scrutiny, introducing to the research apparatus the notion of the pre-text that is composed of different versions of the text and all notes and amendments of the author that surround the manuscript. All those variants, and not the text itself, that is called the ultimate text, constitute the key to understand the process of creation and the discovery of an alternative history of literature as opposed to the one that has been established solely on the basis of printed output of authors. The Różański Archive, currently held in the collection of the House of Literature at the Municipal Raczynski Library in Poznan, is composed of virtually hundreds of unpublished poems, still in hand-written form, written by the poet. In all, they constitute an excellent material for analysis and, possibly, a prospective genetic edition, a concept of which, in relation to inedits (unpublished materials),has been proposed by the French theoretician Pierre-Marc de Biasi.
The literary archives of Wincenty Różański in view of the assumptions of genetic criticism
Keywords: Wincenty Różański – spuścizna literacka; Biblioteka Raczyńskich – zbiory; krytyka genetyczna; przed-tekst; Wincenty Różański – literary output; Raczynski Library – collections; genetic criticism; pre-text